Injury from a Bladed Weapon (IBW) in cervical region with airway involvement: Case report (Research, Society and Development, 2025)
Introduction: Penetrating neck injuries (PNIs) are serious injuries that rupture the platysma muscle, and are dangerous due to their proximity to vital structures. They represent up to 10% of traumas in adults, with a predominance of stab wounds. This article aims to present a case study of stab wounds in the cervical region with airway compromise. Discussion: It is the responsibility of the emergency physician and the pre-hospital care team to stabilize and transport these patients to the operating room. Hemostasis must be ensured, and for external bleeding, digital compression should be applied, possibly using a Foley balloon catheter. Furthermore, airway patency must be maintained by inserting a tracheostomy or endotracheal tube through the wound opening; if the wound diameter is smaller, expand it as needed. If endotracheal intubation fails, tracheostomy should be performed on the second attempt. If airway loss is caused by anatomical abnormalities or hematomas, cricothyroidotomy is an alternative, as the higher incision minimizes the influence of hematomas. Conclusion: This report highlights the urgency of the initial approach and the complexity of pressure ulcers. Further training of emergency teams and more research are needed to standardize the management of lesions in Zone II, the region with the highest incidence, which suffers from controversies in its management, and which also has the best surgical approach and the most favorable prognosis.